Turnover in Life-Strategies Recapitulates Marine Microbial Succession Colonizing Model Particles - Pascual-García, Alberto; Schwartzman, Julia; Enke, Tim N.; Iffland-Stettner, Arion; Cordero, Otto X.; Bonhoeffer, Sebastian (Frontiers in Microbiology, 2022)
Particulate organic matter (POM) in the ocean sustains diverse communities of bacteria that mediate the remineralization of organic complex matter. However, the variability of these particles and of the environmental conditions surrounding them present a challenge to the study of the ecological processes shaping particle-associated communities and their function. In this work, we utilise data from experiments in which coastal water communities were grown on synthetic particles to ask which are the most important ecological drivers of their assembly and associated traits. Combining 16S rRNA amplicon sequencing with shotgun metagenomics, together with an analysis of the full genomes of a subset of isolated strains, we were able to identify two-to-three distinct community classes, corresponding to early vs. late colonizers. We show that these classes are shaped by environmental selection (early colonizers) and facilitation (late colonizers), and find distinctive traits associated with each class. While early colonizers have a larger proportion of genes related to uptake of nutrients, motility and environmental sensing with few pathways enriched for metabolism, late colonizers devote a higher proportion of genes for metabolism, comprising a wide array of different pathways including metabolism of carbohydrates, amino acids and xenobiotics We find evidence in selected metabolic pathways for the existence of a trophic-chain topology connecting both classes. The interpretation of these traits suggests a distinction between early and late colonizers analogous to other classifications found in the literature, and we discuss connections with the classical distinction between r- and K-strategists